(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
This paper aims to characterize the management skills that include the leaders of midsize businesses in the Colombian Caribbean region and how these contribute to exercise their tasks and the impact on a competitive management. The type of study used was the exploratory-descriptive one. To carry out this work it was designed a 18-question instrument that allowed measuring managerial skills of leaders of midsize businesses in the Colombian Caribbean region, this instrument was applied to 252 leaders of midsize businesses, allowing to identify the characteristics of the leaders, their ways of conduct and behavior among others; It can generally conclude that leaders are clear about what this concept means, they have a relational leadership profile, they use a greater proportion of oral communication, they are characterized more by listening and observing, they behave as reagent leaders, very busy with high stress levels.